Canciones de Pío peep! [compact disc] : rimas tradicionales en español - Ada, Alma Flor; Campoy, F. Isabel; Schertle, Alice; Paz, Suni (HarperCollins, 2006)
A collection of more than a dozen nursery rhymes in Spanish, from Spain and Latin America on the CD, along with more than two dozen rhymes in the book in Spanish with English translations.